2023
DOI: 10.3390/cancers15133417
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Chronic Low Dose Rate Total Body Irradiation on the Heart Proteome of ApoE−/− Mice Resemble Premature Cardiac Ageing

Omid Azimzadeh,
Juliane Merl-Pham,
Vikram Subramanian
et al.

Abstract: Recent epidemiologic studies support an association between chronic low-dose radiation exposure and the development of cardiovascular disease (CVD). The molecular mechanisms underlying the adverse effect of chronic low dose exposure are not fully understood. To address this issue, we have investigated changes in the heart proteome of ApoE deficient (ApoE−/−) C57Bl/6 female mice chronically irradiated for 300 days at a very low dose rate (1 mGy/day) or at a low dose rate (20 mGy/day), resulting in cumulative wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Sridharan et al [ 16 ] compared cardiac changes (e.g., plasma metabolomics, collagen deposition, mast cell numbers, and Toll-like receptor 4 expression) in wild-type mice whose whole hearts or partial (40%) hearts received irradiation, and observed no difference in adverse tissue remodeling in the irradiated and unirradiated parts of the heart. Azimzadeh et al [ 17 ] conducted proteomic analysis in the heart of apolipoprotein E-deficient mice of which whole bodies were continuously exposed at 1 mGy/day or 20 mGy/day, and found that such chronic irradiation modulates various pathways in the heart that are common with age-related pathways. Hamada et al [ 18 ] used four different irradiation regimens to deliver the same total dose, and found that the magnitude of damage arising at 12 months post-irradiation in the aorta of whole body-irradiated wild-type mice was greater in 25 fractions, smaller in 100 fractions, and much smaller in chronic exposure (at ca.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sridharan et al [ 16 ] compared cardiac changes (e.g., plasma metabolomics, collagen deposition, mast cell numbers, and Toll-like receptor 4 expression) in wild-type mice whose whole hearts or partial (40%) hearts received irradiation, and observed no difference in adverse tissue remodeling in the irradiated and unirradiated parts of the heart. Azimzadeh et al [ 17 ] conducted proteomic analysis in the heart of apolipoprotein E-deficient mice of which whole bodies were continuously exposed at 1 mGy/day or 20 mGy/day, and found that such chronic irradiation modulates various pathways in the heart that are common with age-related pathways. Hamada et al [ 18 ] used four different irradiation regimens to deliver the same total dose, and found that the magnitude of damage arising at 12 months post-irradiation in the aorta of whole body-irradiated wild-type mice was greater in 25 fractions, smaller in 100 fractions, and much smaller in chronic exposure (at ca.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
“…Therefore, this Special Issue ( ) aims to serve as a forum to gather the latest developments and discuss future prospects in the field of normal tissue responses to radiation exposure. The Special Issue consists of 18 articles [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] outlining the cancer and non-cancer effects of radiation occurring in various tissues (e.g., those in the circulatory, sensory, nervous, respiratory, and reproductive systems), including studies on mitigation strategies and biomarkers, as outlined below.…”
Section: Introductionmentioning
confidence: 99%